2022
DOI: 10.1111/gwao.12843
|View full text |Cite
|
Sign up to set email alerts
|

Maternity provision, contract status, and likelihood of returning to work: Evidence from research intensive universities in the UK

Abstract: Reliance on fixed-term contracts and a lack of adequate maternity provision for fixed-term workers could be contributing to the loss of women from academia-the so called "leaky pipeline"-but evidence on this is lacking. This paper describes variation, between research intensive universities in the UK, in the maternity provision they offer to fixed-term workers and presents preliminary staff data on the likelihood of returning to work following a period of maternity leave for academic and non-academic staff on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 53 publications
0
4
0
1
Order By: Relevance
“…To support cultural change, language used in both policy and practice should reflect the fact that maternity leave is a perfectly normal and positive aspect of life and actively supported throughout the organization. Another way to support and demonstrate a cultural shift is through more progressive university policies, such as maternity provision for fixed contract workers along the lines proposed by Davies et al (2022) and extensions to track tenure or other types of major institutional evaluation that represent the true time cost of maternity leave. Other innovative solutions, along the lines of returner schemes, would fund and protect time and research support to enable women to re-engage with academic work considered crucial for future career success, such as publications and grant writing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To support cultural change, language used in both policy and practice should reflect the fact that maternity leave is a perfectly normal and positive aspect of life and actively supported throughout the organization. Another way to support and demonstrate a cultural shift is through more progressive university policies, such as maternity provision for fixed contract workers along the lines proposed by Davies et al (2022) and extensions to track tenure or other types of major institutional evaluation that represent the true time cost of maternity leave. Other innovative solutions, along the lines of returner schemes, would fund and protect time and research support to enable women to re-engage with academic work considered crucial for future career success, such as publications and grant writing.…”
Section: Discussionmentioning
confidence: 99%
“…A recent analysis of 24 research‐intensive university policies found similarly limited enhanced maternity pay for fixed‐term workers who face redundancy during maternity leave and/or do not have a record of continuous employment. The study also found that the odds of returning to work after maternity leave were lower for staff on fixed‐term contracts compared to open‐ended contracts, indicating that lack of appropriate maternity provision contributes to the leaky pipeline in academia (Davies et al., 2022). Although most countries provide statutory paid maternity/paternity leave, the main exception being the United States, this tends to be more generous in Nordic, Central, and Eastern European OECD countries compared to the UK which offers one of the lowest rates of statutory maternity pay followed only by Ireland (OECD, 2022).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Universities are also considered gendered and raced institutions (Mihăilă, 2018;Salmon, 2021), which individuals experience through gendered advantage and disadvantage (Pullen, Rhodes, & Thanem, 2017). Organised around a masculine 'ideal' academic with no caring responsibilities (Benschop & Brouns, 2003;Martinovic & Verkuyten, 2013;Mauthner & Edwards, 2010), careers in universities remain problematic for women (Ashencaen Crabtree & Shiel, 2019;Davies, Brighton, Reedy, & Bajwah, 2022;Reedy & Haynes, 2021) or those classed as 'other' to the idealised norms (Bleijenbergh, Van, & Vinkenburg, 2012). Such positioning influences our subjectivity, ontology and hence our self-reflexivity.…”
Section: Being Struckmentioning
confidence: 99%
“…En este contexto, se debe además considerar que el mérito entrega una clave para comprender cómo el académico ideal y su contraparte menos ideal se configuran como creaciones de género (Thornton, 2013), específicamente porque la idea de la meritocracia oculta prácticas de desigualdad que nada tienen que ver con el mérito: el género se manifiesta en las evaluaciones académicas con desventajas para las mujeres y privilegios para los hombres, los que se acumulan para generar desigualdades en la construcción de la excelencia académica (van den Brink & brechas de género en la productividad científica Benschop, 2011). Por consiguiente, a pesar del desarrollo de la igualdad de oportunidades en las universidades, la imagen del académico ideal continúa configurándose a la imagen de un hombre como referencia (Thorton, 2013), quien además puede jugar fácilmente dentro de las reglas del juego académico (Davies et al, 2022).…”
Section: Contexto De La Educación Superior Y La Mujer En La Academiaunclassified